If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + 2) = 14 Reorder the terms: 2(2 + t) = 14 (2 * 2 + t * 2) = 14 (4 + 2t) = 14 Solving 4 + 2t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2t = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 2t = 14 + -4 2t = 14 + -4 Combine like terms: 14 + -4 = 10 2t = 10 Divide each side by '2'. t = 5 Simplifying t = 5
| 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 | | 8y+2=4x | | 3x+20=41 | | X+(-3)+9=-1+14 | | h(t)=-4.9t^2+24t+8 | | 4x^7-32x^5= | | 34+20=41 | | 2x-38=180 | | x^2+24-11x= | | 27=7+4w | | e^10x+6=12 | | 9a+27= | | 17=-5m+3 | | 5(y+4)=8y-45 | | 4x+7x-38=76-8x | | 3a+2w-5a-9w= | | 7+24m=28+17m | | 8x-3y=37 | | 16x^4-16x^3+4x^2=0 |